PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN DI INDOMARET CIGOMBONG SUKABUMI JAWA BARAT - Gena (Sekolah Tinggi Ilmu Ekonomi GICI, 2023)
Consumer satisfaction is a very important factor that must be considered by companies so that consumers want to come back. Service quality is an important factor that must be considered by companies to get customer satisfaction. Service quality is the key to the success of a company, especially in the retail sector. Good service quality can be a competitive advantage for retail companies. In addition to service quality, price perception is also an important factor that must be considered by companies, especially in the form of retail. Companies must always monitor prices set by competitors, so that the prices set by the company are not too high, so as to create customer satisfaction. The purpose of this study is to determine and analyze the Effect of Service Quality and Price on Consumer Satisfaction in Indomaret Cigombong. The type of research used is explanatory research with research methods in the form of data collection using questionnaires. The data analysis model used is multiple linear regression analysis. Sample selection is done by purposive sampling. The sample amounted to 100 respondents, using multiple linear regression analysis. The results of the Coefficient of Determination test showed that 42.70% of consumer satisfaction factors could be explained by service quality and price while the remaining 57.30% was explained by other factors not studied in this study. While the results of the F test show that simultaneously the variables of service quality and price simultaneously have a positive and significant effect on consumer satisfaction with the results of the analysis, namely the value of Fcalculate (37,814) > Ftable (3,900). The results of the t test show that the service quality variable shows the results of the tcalculate analysis (5.671) and the price variable shows the results of the tcalculate analysis (4.889) where ttable (1.984), then partially the two variables have a positive and significant effect on consumer satisfaction at Indomaret Cigombong. Price is the most dominant variable affecting consumer satisfaction in Indomaret Cigombong, Bogor Regency.